Peningkatan Kecerdasan Emosional Anak Inklusif melalui Metode Hypnoteaching di PAUD Aulia Cimahi - Nafiqoh, Heni; Rohmalina, Rohmalina; Fatimah Zahro, Ifat (ACIECE, 2019)
This study raises the issue of "Increasing Emotional Intelligence of Inclusive Children throughHypnoteaching Method in Aulia Cimahi PAUD". The goal expected through this research is todescribe and find out the process of applying hypnoteaching methods to improve emotionalintelligence of PAUD Aulia Cimahi children. used in this research is a qualitative researchapproach. Hypnoteaching method is a reference to appropriate learning methods used inincreasing emotional intelligence, Hypnoteaching method. Hypnoteaching combining fiveexisting methods in learning, namely QL (quantum learning), AL (accelerate learning), PT (powerteaching), NLP (Neuro-Linguistic Programming) and hypnosis. Hypnoteaching method is learningthat emphasizes communication under the student's conscious mind, which is done both in theclassroom and outside the classroom in various ways such as suggesting and inspiring. To thatend, educators are expected to master this hypnoteaching method as one of the learningmethods in schools in delivering learning that is in accordance with the six aspects of childdevelopment through suggestions that are passed on to the brain and stimulate in order tooptimally increase the emotional intelligence of students. The results of this study describe thatthe results obtained through observation shows satisfying results. By using the hypnoteachingmethod in learning emotional intelligence, the results of the research that has been carried out,it can be concluded that the teacher has been able to apply the hypnoteaching method so thatthe learning activities carried out can take place with an interesting, enjoyable and learningobjectives can be achieved